(untitled) (Journal of Foreign Language Studies, 2022)
In Vietnamese, time expressions are not determined by the suffixes in languages with clear temporal references. Expression of time in Vietnamese is a lexical-grammatical category that operates in the "implicit" and "thrifty" mechanism. This mechanism lies first in the general and universal linguistic thinking. Through a survey on several Japanese works translated into Vietnamese and Vietnamese works translated into Japanese, this study points out certain characteristics related to the time expression of the Japanese and the corresponding relationship in terms of tenses between the two distinct languages: Japanese and Vietnamese. The research findings contribute to the improvement of learning and more effective use of the Japanese language.